Quality of Life among Post-Mastectomy with and without Reconstruction Breast Cancer Patients in Onkologi Surabaya Hospital - Cindy Angelina Limantara; Ario Djatmiko (National Cancer Center - Dharmais Cancer Hospital, 2021)
Background: The quality of life (QoL) of breast cancer (BCa) patients is an outcome of therapy that is often overlooked. In real life, postoperative breast cancer patients experience deep trauma in view that breasts are a symbol of femininity, which are very valuable for any female. This study aims to compare the QoL in patients who received mastectomy only and mastectomy with reconstruction.Methods: A retrospective comparative study of 25 post-mastectomy to 25 post-mastectomy with reconstruction BCa patients in Onkologi Surabaya Hospital. The subjects are patients who visited between July 2019 until March 2020, as many as 50 samples in accord with the inclusion and exclusion criteria. The assessment was performed using 3 instruments, including the hospital anxiety and depression scale (HADS), body image scale (BIS), and female sexual function index (FSFI). The collected data were analyzed using SPSS 15.0 for Windows.Results: A significant difference in mean values was seen in body image and sexual function. Post-mastectomy BCa patients presented more body image disturbance (p < 0.05). Better sexual function is claimed by post-mastectomy with reconstruction BCa patients in Onkologi Surabaya Hospital (p < 0.05). Meanwhile, the depression and anxiety values did not differ significantly in both groups (p > 0.05).Conclusions: Patients who underwent mastectomy and breast reconstruction have a better QoL in comparison with patients who received mastectomy only, in the domains of body image and sexuality function.